Exploitation of Phenotypic Variations Among some Barley (Hordeum vulgare L.) Genotypes for grain yield Under Irrigated Conditions of Sudan - Jassir, Jassir F. F.; Elhashimi, Ashraf M. A.; Babiker, Sara A. E.; Ali, Eltahir S. (Gezira Journal of Agricultural Science, 2020)
Barley in Sudan is grown in limited areas for grain and forage, although the barley is a well adapted crop to Sudan environment, it has a very small number of genotypes. Therefore, this study aims at the exploitation of  phenotypic variations among the barley ( Hordeum vulgare L.) genotypes in Sudan for possible utilization in breeding programmes and to identify the top yielding genotypes. A set of twenty barley genotypes were tested at three sites representing different environments of Sudan. The experiments were executed over two consecutive seasons (2010/2011 and 2011/2012) in a Randomized Complete Block Design (RCBD) with three replications. The results of the growth habit demonstrated that all the genotypes were resistant to lodging except the genotype 20 (local genotype) was susceptible to lodging. The results of the combined analysis showed very highly significant differences among the barley genotypes at three sites. Across the three sites, the common genotypes out-yielded the check were G3, G8 and G9. At Gezira, the genotypes G3, G8 and G9 out yielding the check by 31, 24 and 40%, respectively, at Hudeiba high terrace soil by 34, 9 and 31%, respectively, while at Hudeiba karu soil by 61, 21 and 20%, respectively. According to the ASV (AMMI Stability Value) concept, the most stable genotype was the check Beladi having an ASV of 4.5 with the lowest mean seed yield (1970 kg/ha). In contrast, the most unstable genotype was G3 with an ASV of 37.7, however, it had the highest grain yield (2810 kg/ha). Among the six environments, when the genotypes were arranged according to AMMI estimate, genotype G3 ranked first in four environments (Gezira in season 2011, karu in two seasons and high terrace soil in season 2011), genotype G9 ranked first in one environment (Gezira in season 2010) and ranked third in the other five environments, while genotype G8 ranked second in the high terrace soil in season 2010 and fourth in two environments (Gezira in two seasons). The check Beladi did not appear in the first four ranking genotypes. Therefore, the genotypes G3, G8 and G9 could provide a good option for barley seed yield under Sudan conditions.   يزرع الشعير في السودان في مناطق محدودة بغرض إنتاج الحبوب والأعلاف، على الرغم من أن الشعير محصول جيد التأقلم  في البيئات المناخية المختلفة  للسودان، إلا أن هنالك عددا قليلا جدًا من الطرز الوراثية التي تزرع فيه. لذلك، تهدف هذه الدراسة إلى إستغلال الاختلافات المظهرية بين بعض الطرز الوراثية للشعير ( Hordeum vulgare L.) في السودان لإمكانية استخدامها في برامج التربية ولتحديد الطرز الوراثية الاعلي إنتاجية. تم اختبار عدد عشرين من الطرز الوراثية للشعير في ثلاثة مواقع تمثل بيئات مختلفة في السودان. تم تنفيذ التجارب على مدار موسمين متتاليين (2010/2011 و 2011/2012) باستخدام تصميم القطاعات العشوائية الكاملة (RCBD) بثلاثة مكررات. أظهرت نتائج التحليل المشترك تباين كبير للغاية بين الطرز الوراثية للشعير من حيث الإنتاجية في الثلاثة مواقع، حيث كانت الطرز الوراثية الشائعة التي فاقت إنتاجيتها الصنف المحلي هي G3 و G8 و G9 . في الجزيرة، الطرز الوراثية G3 و G8 و G9 فاقت إنتاجيتها الصنف المحلي بنسبة 31 و 24 و 40٪ على التوالي، أما في أراضي التروس العليا (الحديبة)  بنسبة 34 و 9 و 31٪ على التوالي، بينما في أراضي الكرو (الحديبة) بنسبة 61 و 21 و 20٪، على التوالي. وفقًا لمفهوم قيمة الثبات (ASV) كان الطراز الوراثي الأكثر ثباتًا هو الصنف المحلي بقيمة ثبات4.5  وبأقل متوسط ​​إنتاجية للبذور (1970 كجم / هكتار). في المقابل، كان الطراز الوراثي الأقل ثباتًا هو       G3 بقيمة ثبات  37.7، ومع ذلك، فقد حقق أعلى إنتاجية للحبوب (2810 كجم / هكتار). عند ترتيب الطرز الوراثية وفقًا لتقدير  AMMI في البيئات الست، احتل الطراز الوراثي G3 المرتبة الأولى في أربع بيئات (الجزيرة في موسم 2011 ، اراضي الكرو (الحديبة) في موسمين وفي اراضي التروس العليا (الحديبة) في موسم 2011) ، بينما احتل الطراز الوراثي G3  المرتبة الأولى في بيئة واحدة (الجزيرة) في موسم 2010) واحتل المرتبة الثالثة في البيئات الخمسة الأخرى، في حين احتل الطراز الوراثي G8 المركز الثاني في اراضي التروس العليا (الحديبة) في موسم 2010 والرابع في بيئتين (الجزيرة في موسمين). لم يظهر الصنف المحلي ضمن الطرز الوراثية الأربعة الأولى. أوضحت هذه النتائج أن الطرز الوراثية  G3 و G8 و G9 يمكن أن تكون خيارًا جيدًا لإنتاج بذور الشعير تحت ظروف السودان